The impact of adverse childhood experiences and posttraumatic stress symptoms on chronic pain - Stapleton, Peta; Kang, Yage; Schwarz, Robert; Freedom, John (Frontiers in Psychology, 2023)
Chronic pain is a prevalent worldwide health condition. The current study aimed to extend previous research that investigated the dynamics between chronic pain, adverse childhood experiences (ACEs), and post-traumatic stress symptoms (PTSS;Beal et al., 2020;Marin et al., 2021). Adult participants worldwide with chronic pain were recruited for this study (N = 199; 89% females). Three hypotheses were proposed: (a) a high ACEs score would result in more severe pain intensity and interference compared to no ACEs; (b) a low ACEs score would result in more severe pain intensity and interference compared to no ACEs; and (c) PTSS would fully mediate the ACEs-pain relationship. Initially results indicated individuals with high ACEs reported more pain interference than those with no ACEs, although pain intensity did not differ between high and no ACEs. However, after controlling for age, socioeconomic status (SES), and pain duration, low and high ACEs were not significantly associated with pain intensity or interference compared to no ACEs. However, SES status was associated with pain intensity and interference, although not with pain interference after adding low and high ACEs to the model.Because of this the mediation exploration of PTSS was not viable. Implications for practice, limitations and future research outcomes are outlined.